Mapping a collaborative cartography of the encounters between the neurosciences and early childhood education practices. Issue 2 (4th March 2018) - Aronsson, Lena; Lenz Taguchi, Hillevi
ABSTRACT: This paper takes its starting point in a shared problem of concern, formulated in terms of what might be produced – or not – as effects of encounters between neuroscientific research and preschool practices. The aim is to show what emerged in collaborative encounters, in what is theorized and practised as Deleuzo–Guattarian-inspired cartography mapping exercises. During regularly scheduled staff 'reflection meetings', an invited doctoral student enacted, participated, and documented these encounters with preschool staff at three preschools in the same area outside Stockholm, Sweden. Two major lines of articulation, converging around a core problem, were collaboratively constructed and put on this 'map'. These were then actively put to play to be disrupted and deterritorialized, making ways for new diverging lines and potential reconfigured forms of literacy practices.